Nutritional and Microbiological Evaluation of Market-Sourced Ready-to-Eat Snail Meat in Delta, Edo, and Ondo States, Nigeria - I Ogu, Gideon; Ereziwosa, Beatrice O. (Journal of Food and Pharmaceutical Sciences, 2025)
Snail meat is a popular delicacy in Nigeria, cherished for its taste, nutritional composition, and culinary versatility. However, the safety and quality of ready-to-eat snail meat (RTESM) have not been extensively studied. This research aimed to evaluate the chemical and microbiological quality of ready-to-eat snail meat in three southern Nigerian states: Delta, Edo, and Ondo. A total of 60 samples were collected from open markets in these regions and analyzed for proximate, trace metals and microbiological properties using standard techniques. The proximate analysis revealed non-significant (p˂0.05) variations in moisture, fat, protein, ash, crude fiber, and carbohydrate contents among the samples from different locations. Akure and Benin City RTESM samples showed higher moisture content (51.34 - 52.28), while Warri samples had higher fat (13.56 %) and protein (24.22 %) contents. Akure samples exhibited higher ash (10.48 %) and carbohydrate (9.86 %) contents. Appreciable amountof essential metals in the RTESM were observed and highlight its potential as a valuable dietary component. Potential foodborne bacteria, including Listeria spp. (6.7 %), Salmonella spp., (15.0 %), Escherichia coli (25.0 %), and Staphylococcus aureus (53.3 %) were detected and pose some public health concerns. Findings from this study provide valuable insights into the chemical and microbiological quality of RTESM in southern Nigeria. The variations observed in chemical composition and the presence of potentially harmful microorganisms emphasize the need for implementation of good hygiene practices throughout the production and processing chain to ensure the safety and nutritional value of snail meat products.